Preserving community through translation: A case study of a fandom community translation - Marroquin Paitan, Diana Isabel (2024)
This research analyzes the process of a community translation conducted by a group of Hispanic-American fans of a book from the young-adult fantasy saga Shadowhunters. The Shadowhunters’ fandom criticized the Spanish translation of a transnational publishing house for having altered the content and delayed the translation. Faced with the poor reception of the translated product, some members of the fandom gathered on Facebook to generate a translation that would satisfy their community. This process is reconstructed through digital ethnography. It describes how the group of translators generated coordination spaces for the team as well as a meeting place with the community, which would function as spaces for literacy. In said spaces, a translation method consistent with the social objectives of the fandom was built by performing a rapid translation through a process with simultaneous stages, encouraging member learning, maintaining motivation, and commitment through affective communication.